EFEKTIVITAS PENERAPAN INOVASI PELAYANAN PUBLIK DALAM PENGEMBANGAN E-GOVERNMENT ( Studi Kasus Aplikasi Sp4n Lapor! Di Provinsi Sumatera Selatan ) - Riska Fakhriyah; Novia Kencana; Muhammad Qurâ€™anul Kariem (Jurnal Pemerintahan dan Politik, 2022)
Â This paper discusses the effectiveness of the application of SP4N LAPOR! in South Sumatra Province. The purpose of this study was to determine the effectiveness and usefulness of the application made by the government, namely the SP4N LAPOR! in South Sumatra Province. The approach used in this research is descriptive research, which is a type of research that seeks to describe phenomena/events as they are. The research method used in this research is qualitative research. Qualitative research is a research and understanding process based on a methodology that investigates a social phenomenon and human problem based on data. Data collection methods used to collect data in qualitative research generally use observation, interviews, and documentation studies. The research uses the Effectiveness theory of Campbell JP which states that there are four factors, namely program success, target success, output and input levels, and the last is the achievement of overall goals. Based on the results of the research and discussion conducted, the researcher can conclude about the effectiveness of the application of the SP4N LAPOR! in South Sumatra Province, it is said that it has not been effective as seen from less than 70% of archived reports than those that have been completed and 84% of the public do not know the existence of this application. The suggestion from this research is that the government of South Sumatra, in this case the Department of Communication and Information, should be more routine in conducting socialization related to the application and procedures for using the SP4N LAPOR! by optimizing the role of social media, conducting socialization in the sub-district office/lurah as well as conducting socialization among students.Keywords : Effectiveness, Public Service Innovation, SP4N LAPOR! Application